Development and characterization of type I interferon receptor knockout sheep: A model for viral immunology and reproductive signaling - Davies, Christopher J.; Fan, Zhiqiang; Morgado, Kira P.; Liu, Ying; Regouski, Misha; Meng, Qinggang; Thomas, Aaron J.; Yun, Sang-Im; Song, Byung-Hak; Frank, Jordan C.; Perisse, Iuri V.; Van Wettere, Arnaud; et al. (Frontiers in Genetics, 2022)
Type I interferons (IFNs) initiate immune responses to viral infections. Their effects are mediated by the type I IFN receptor, IFNAR, comprised of two subunits: IFNAR1 and IFNAR2. One or both chains of the sheep IFNAR were disrupted in fetal fibroblast lines using CRISPR/Cas9 and 12 lambs were produced by somatic cell nuclear transfer (SCNT). Quantitative reverse transcription polymerase chain reactions for IFN-stimulated gene expression showed that IFNAR deficient sheep fail to respond to IFN-alpha. Furthermore, fibroblast cells from an IFNAR2–/– fetus supported significantly higher levels of Zika virus (ZIKV) replication than wild-type fetal fibroblast cells. Although many lambs have died from SCNT related problems or infections, one fertile IFNAR2–/– ram lived to over four years of age, remained healthy, and produced more than 80 offspring. Interestingly, ZIKV infection studies failed to demonstrate a high level of susceptibility. Presumably, these sheep compensated for a lack of type I IFN signaling using the type II, IFN-gamma and type III, IFN-lambda pathways. These sheep constitute a unique model for studying the pathogenesis of viral infection. Historical data supports the concept that ruminants utilize a novel type I IFN, IFN-tau, for pregnancy recognition. Consequently, IFNAR deficient ewes are likely to be infertile, making IFNAR knockout sheep a valuable model for studying pregnancy recognition. A breeding herd of 32 IFNAR2+/– ewes, which are fertile, has been developed for production of IFNAR2–/– sheep for both infection and reproduction studies.